Monetary Authorities - Lumba, Allan (Duke University Press, 2022)
Allan E. S. Lumba explores how the United States used monetary policy and banking systems to justify racial and class hierarchies, enforce capitalist exploitation, and counter movements for decolonization in the American colonial Philippines.